Recent advances, advantages and limitations of genetically modified foods - Abbas, Kassim Ali; Olusegun, Lasekan; Khalil, Sahar K. (Wfl Publisher, 2010)
Despite the potential benefits of genetically modified foods (GMF), the technology has its limitations and is surrounded by controversy. This review focuses on the recent advances and applications of GM in food production, the present advantages of GMF as well as its limitations and challenges in safety assessment evolving from the recent developments. By summarizing the published information from scattered references in the literature, this paper attempts to contribute to the literature an overall understanding as well as the current status evolution of this field.